Diagnostic accuracy of the MMPI-2 with the Mexican criminal personality: The ROC curve analysis - Ampudia Rueda, Amada (2017)
The objective of this study is to assess the diagnostic accuracy of the personality of the Mexican criminal with the Minnesota Multiphasic Personality Inventory-2 (MMPI-2). The inventory was administered to 1,740 Mexican participants of which 870 (728 male and 142 female) are prison inmates, processed and/or sentenced for various crimes from various prisons in Mexico City, and the other 870 participants (728 male and 142 female) are not prison inmates. The ROC (Receiver Operating Characteristic) curve analysis was used to assess the level of diagnostic accuracy through indexes of the Area below the curve (ABC), sensitivity (S) and specificity (E). The analysis was differentiated by gender and showed significant differences